Porous phosphorus-based sodium ion battery alloy negative electrode material and preparation method thereof

By preparing porous sodium ion battery alloy negative electrode material, the problem of insufficient performance of the negative electrode material of sodium ion battery is solved, high porosity and excellent electrochemical performance are achieved, and the overall performance of the battery is improved.

CN119733830AActive Publication Date: 2025-04-01SHENZHEN JANAENERGY TECH CO LTD +1

Patent Information

Application Number
CN202411792964.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-08
Publication Date
2025-04-01
Estimated Expiration
2044-12-08

AI Technical Summary

Technical Problem

Research on negative electrode materials of sodium ion batteries is progressing slowly. Existing hard carbon materials have low capacity, low initial Coulomb efficiency and poor rate performance, while phosphorus-based materials face the challenges of poor conductivity and large volume expansion.

Method used

By preparing the porous sodium phosphorus-based ion battery alloy negative electrode material, the porous phosphorus-based alloy material with a gradient structure is formed by alloying the red phosphorus and sodium-embedded metal powder and high-temperature calcination pore formation method.

Benefits of technology

It realizes adjustable material structure and morphology, high porosity and excellent electrochemical performance, improves the energy density and power density of the battery, and improves the cycle stability and specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733830A_ABST
    Figure CN119733830A_ABST
Patent Text Reader

Abstract

The invention discloses a porous phosphorus-based sodium ion battery alloy negative electrode material and a preparation method thereof, and the preparation method comprises the following steps: S1, raw material mixing: weighing red phosphorus and sodium-embedded metal powder, and uniformly mixing in proportion to obtain raw material powder; s2, alloying treatment is conducted, specifically, the raw material powder is subjected to ball milling under the protective atmosphere for alloying, and phosphorus-based alloy powder is formed; and S3, calcining and pore-forming: carrying out high-temperature calcining and pore-forming on the phosphorus-based alloy powder in a protective atmosphere to form porous phosphorus-based alloy powder, and cooling to obtain the porous phosphorus-based sodium-ion battery alloy negative electrode material. The preparation method of the porous phosphorus-based sodium ion battery alloy negative electrode material has the characteristics of adjustable material structure and morphology, high porosity and excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery materials, and in particular to a porous phosphorus-based sodium ion battery alloy negative electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been the dominant technology in the field of energy storage due to their excellent energy density and relatively stable cycle performance. However, the scarcity and uneven distribution of lithium resources limit their potential for large-scale application and cost control. At the same time, sodium-ion batteries have attracted attention due to their similar physical and chemical properties to lithium-ion batteries. Sodium is abundant in the earth's crust, widely distributed, and relatively low in cost, which makes sodium-ion batteries show obvious advantages in the sustainable utilization of resources.

[0003] Although sodium-ion batteries have great potential in theory, there are still many challenges to overcome in practical applications. At present, the research on positive electrode materials for sodium-ion batteries has made significant progress, and a variety of materials with excellent electrochemical properties have been developed.

[0004] In contrast, the research progress of anode materials for sodium-ion batteries has been slow. The performance of anode materials has a direct impact on the capacity, cycle stability and charging efficiency of the battery. An ideal anode material should have a low charge and discharge voltage platform, high specific capacity and good cycle stability. Although hard carbon materials have been commercialized, there are still some challenges, such as low capacity (usually less than 350 mAh / g), low initial coulombic efficiency and poor rate performance.

[0005] Phosphorus-based materials are considered important candidates for negative electrode materials for sodium-ion batteries due to their high theoretical specific capacity (2596 mAh / g), abundant reserves, and low prices. However, phosphorus-based materials face challenges of poor conductivity and large volume expansion in practical applications, which limits their performance as negative electrode materials. Compounding them with other metals to obtain phosphorus-based alloy materials can alleviate this problem to a certain extent. However, when compounded with sodium-embedded metals, the sodium-embedded metals themselves also have huge volume expansion, causing the material structure to collapse. Summary of the invention

[0006] The purpose of the present invention is to provide a porous phosphorus-based sodium ion battery alloy negative electrode material and a preparation method thereof, which has the characteristics of adjustable material structure and morphology, high porosity and excellent electrochemical performance.

[0007] The present invention can be implemented by the following technical solutions: The present invention discloses a method for preparing a porous phosphorus-based sodium ion battery alloy negative electrode material, comprising the following steps: S1. Raw material mixing: weigh red phosphorus and sodium-embedded metal powder and mix them evenly in proportion to obtain raw material powder; S2. Alloying treatment: alloying the raw material powder by ball milling under a protective atmosphere to form a phosphorus-based alloy powder; S3. Calcination and pore formation: The phosphorus-based alloy powder is calcined at high temperature under a protective atmosphere to form pores to form porous phosphorus-based alloy powder. After cooling, a porous phosphorus-based sodium ion battery alloy negative electrode material can be obtained.

[0008] The present invention synthesizes porous alloy materials. The presence of pores can provide expansion space for phosphorus and composite metals. The porous structure can increase the specific surface area of ​​the material, thereby providing more active sites, which helps to increase the transmission rate of electrons and ions. This structural characteristic is crucial to improving the energy density and power density of the battery.

[0009] Further, in step S3, the calcination temperature is 590-690°C, the calcination time is 1-4h, and the heating rate is 5-10°C / min. Specifically, regulating the calcination temperature, calcination time and heating rate can optimize the size and distribution of the pores, and a porous phosphorus-based alloy material with a gradient structure can be obtained. When the calcination temperature is low, red phosphorus does not sublimate, and when the calcination temperature is too high, the pore size will be uneven due to the violent sublimation of phosphorus. In the process of phosphorus sublimation, the phosphorus distributed in the outer layer of the powder sublimates first, so controlling the calcination time can control the position of the red phosphorus pores, thereby adjusting the physical and chemical properties of the material. If too little phosphorus is sublimated, the pores obtained are insufficient, and the expansion space provided is insufficient, while too much sublimated red phosphorus will lead to a decrease in the capacity of the phosphorus-based alloy powder.

[0010] Further, in step S2, the mass ratio of the raw material powder to the grinding ball is 1:10-1:20. Specifically, the grinding ball is used to impact and grind the raw material, and is chemically inert and does not react with the raw material. Therefore, the material type is rich, and grinding balls made of materials such as cemented carbide, silicon oxide, zirconium oxide, aluminum oxide, zirconium silicate, stainless steel, agate and ceramic can be used to achieve the purpose of ball milling.

[0011] Furthermore, in the ball milling process, the grinding balls are graded with five diameters of 12mm, 10mm, 8mm, 6mm and 4mm; in terms of mass percentage, the grinding balls with diameters of 12mm and 10mm account for 30%-40%, the grinding balls with diameters of 8mm account for 30%-40%, and the grinding balls with diameters of 6mm and 4mm account for 30%.

[0012] Further, in step S2, the ball milling time is 4-12h, and the ball milling frequency is 40-50Hz. Specifically, during the ball milling process, due to the high-speed vibration of the ball mill, the grinding balls in the ball mill apply strong mechanical force to the powder raw materials, which can cause the powder particles to repeatedly undergo compression, shearing and impact. These mechanical forces increase the contact interface between different powder raw materials and promote the mixing between the raw materials. During the ball milling process, the powder particles will be cold welded under high-energy impact, that is, the particle surfaces are in contact and combined under high pressure. Subsequently, these cold welded particles are broken in subsequent impacts to form finer particles. This process is repeated so that the raw material powders are gradually mixed and alloys are formed. The mechanical force of ball milling can cause deformation and dislocation of the lattice of the powder particles, and can even lead to grain refinement and amorphization. This change in microstructure promotes mixing at the atomic scale, so that different elements are evenly distributed in the lattice to form an alloy. Therefore, the phosphorus in the phosphorus-based alloy powder obtained is evenly distributed in the powder, and the pores formed in situ are also evenly distributed.

[0013] Furthermore, in step S1, the raw materials are mixed in one or more of the following ways: ball milling, grinding, and stirring. The raw materials are mixed uniformly by means of grinding, which is more conducive to the subsequent ball milling process. The uniform and fine operation can be changed according to the actual process conditions. For example, under laboratory conditions, a small grinder or mortar can be used to complete the process; and under industrial processing conditions, a large grinder or grinding equipment can also achieve the same purpose.

[0014] Furthermore, the sodium-intercalating metal powder is antimony powder and / or tin powder. Specifically, antimony and tin themselves have sodium-intercalating activity and can provide more capacity, and the obtained phosphorus-based alloy powder has the advantage of high capacity.

[0015] Further, in step S1, the molar ratio of red phosphorus to antimony powder is 1-2, and the molar ratio of red phosphorus to tin powder is 0.75-4. Specifically, phosphorus itself can provide sodium embedding capacity, and the sublimation of phosphorus during subsequent calcination will reduce the capacity of the porous phosphorus-based alloy material. Therefore, the proportion of phosphorus has a great influence on the cycle stability and capacity of the porous phosphorus-based alloy material. On the basis of ensuring the molar ratio of the target phosphorus-based alloy material, increasing the proportion of phosphorus as a pore-forming agent can retain the material capacity while obtaining a porous structure, but because phosphorus has poor conductivity, an excessively large proportion of phosphorus will lead to a decrease in the overall conductivity of the phosphorus-based alloy material.

[0016] Further, in steps S2 and S3, the protective atmosphere is argon and / or nitrogen.

[0017] Another aspect of the present invention is to protect the porous phosphorus-based sodium ion battery alloy negative electrode material, which is prepared by the above preparation method.

[0018] The present invention is a porous phosphorus-based sodium ion battery alloy negative electrode material and a preparation method thereof, which has the following beneficial effects: First, the material structure and morphology are adjustable. By adopting the calcination method to form pores, the size and distribution of the pores can be optimized by adjusting the calcination temperature, calcination time and heating rate, and a porous phosphorus-based alloy material with a gradient structure can be obtained. In the process of phosphorus sublimation, the phosphorus distributed in the outer layer of the powder sublimates first. Therefore, controlling the calcination temperature, calcination time and heating rate can control the position of the red phosphorus pores, thereby adjusting the physical and chemical properties of the material. Second, the porosity is high. During the calcination and pore-forming process, due to the sublimation of phosphorus, a large number of pore structures are formed in situ, which avoids the additional pore formation steps, simplifies the production process, and increases the porosity and specific surface area of ​​the material, which has potential advantages in improving the electrochemical properties of the material. Third, the electrochemical performance is excellent. The pore structure can provide a buffer space for the volume expansion of the phosphorus-based alloy negative electrode material during the cycle, which is conducive to maintaining the integrity of the material structure. Therefore, the cycle stability of the material is improved. In addition, porous materials usually have a large specific surface area, which provides more active sites for electrochemical reactions, thereby being able to show a higher specific capacity. The porous structure with interconnected channels can establish a continuous charge transfer path in the electrochemical reaction, shorten the ion diffusion path, and promote the acquisition of high capacity at high current density. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The cycle performance curves of Example 1 and Comparative Example 1 at 1000 mA / g are shown; Figure 2 It is the specific surface area test curve of Application Example 2 and Comparative Example 2; Figure 3 is a scanning electron microscope image of Application Example 3; Figure 4 This is a transmission electron microscope image of Application Example 4. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with application examples.

[0021] The present invention discloses a method for preparing a porous phosphorus-based sodium ion battery alloy negative electrode material, comprising the following steps: S1. Raw material mixing: weigh red phosphorus and sodium-embedded metal powder and mix them evenly in proportion to obtain raw material powder; S2. Alloying treatment: alloying the raw material powder by ball milling under a protective atmosphere to form a phosphorus-based alloy powder; S3. Calcination and pore formation: The phosphorus-based alloy powder is calcined at high temperature under a protective atmosphere to form pores to form porous phosphorus-based alloy powder. After cooling, a porous phosphorus-based sodium ion battery alloy negative electrode material can be obtained.

[0022] Further, in step S3, the calcination temperature is 590-690°C, the calcination time is 1-4h, and the heating rate is 5-10°C / min.

[0023] Further, in step S2, the mass ratio of raw material powder to grinding balls is 1:10-1:20.

[0024] Further, in step S2, the ball milling time is 4-12 hours, and the ball milling frequency is 40-50 Hz.

[0025] Furthermore, in step S1, the raw materials are mixed by one or more of ball milling, grinding and stirring.

[0026] Furthermore, the sodium embedded metal powder is antimony powder and / or tin powder.

[0027] Further, in step S1, the molar ratio of red phosphorus to antimony powder is 1-2, and the molar ratio of red phosphorus to tin powder is 0.75-4.

[0028] Further, in steps S2 and S3, the protective atmosphere is argon and / or nitrogen.

[0029] Another aspect of the present invention is to protect the porous phosphorus-based sodium ion battery alloy negative electrode material, which is prepared by the above preparation method.

[0030] Example 1 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh red phosphorus and sodium-embedded metal powder and mix them evenly according to a certain proportion to obtain raw material powder. Specifically, the raw materials are mixed in a manner that the molar ratio of ball-milled red phosphorus to antimony powder is 2.

[0031] S2. Alloying treatment: alloying the raw material powder by ball milling in a protective atmosphere to form a phosphorus-based alloy powder. Specifically, the mass ratio of the raw material powder to the grinding ball is 1:15, the ball milling time is 4 hours, the ball milling frequency is 50 Hz, and the protective atmosphere is argon.

[0032] S3, calcination and pore formation: the phosphorus-based alloy powder is calcined at high temperature under a protective atmosphere to form a porous phosphorus-based alloy powder, and after cooling, a porous phosphorus-based sodium ion battery alloy negative electrode material can be obtained. Specifically, the calcination temperature is 590°C, the calcination time is 2h, the heating rate is 5°C / min, and the protective atmosphere is nitrogen.

[0033] Example 2 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh red phosphorus and sodium-embedded metal powder and mix them evenly according to a certain proportion to obtain raw material powder. Specifically, the raw material mixing method is grinding; the molar ratio of red phosphorus to antimony powder is 1.5.

[0034] S2. Alloying treatment: alloying the raw material powder by ball milling in a protective atmosphere to form a phosphorus-based alloy powder. Specifically, the mass ratio of the raw material powder to the grinding ball is 1:10, the ball milling time is 12 hours, the ball milling frequency is 45 Hz, and the protective atmosphere is nitrogen.

[0035] S3, calcination and pore formation: the phosphorus-based alloy powder is calcined at high temperature under a protective atmosphere to form a porous phosphorus-based alloy powder, and after cooling, a porous phosphorus-based sodium ion battery alloy negative electrode material can be obtained. Specifically, the calcination temperature is 650°C, the calcination time is 1h, the heating rate is 10°C / min, and the protective atmosphere is nitrogen.

[0036] Example 3 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh red phosphorus and sodium embedded metal powder and mix them evenly according to proportion to obtain raw material powder. Specifically, the raw material mixing method is stirring; the molar ratio of red phosphorus to tin powder is 0.75.

[0037] S2. Alloying treatment: alloying the raw material powder by ball milling in a protective atmosphere to form a phosphorus-based alloy powder. Specifically, the mass ratio of the raw material powder to the grinding ball is 1:20, the ball milling time is 8 hours, the ball milling frequency is 40 Hz, and the protective atmosphere is argon and nitrogen.

[0038] S3, calcination and pore formation: the phosphorus-based alloy powder is calcined at high temperature in a protective atmosphere to form pores, and a porous phosphorus-based alloy powder is formed after cooling to obtain a porous phosphorus-based sodium ion battery alloy negative electrode material. Specifically, the calcination temperature is 690°C, the calcination time is 4h, the heating rate is 8°C / min; the protective atmosphere is argon and nitrogen.

[0039] Example 4 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh red phosphorus and sodium-embedded metal powder and mix them evenly according to a certain proportion to obtain raw material powder. Specifically, the raw material mixing method is ball milling; the molar ratio of red phosphorus to tin powder is 2.

[0040] S2. Alloying treatment: alloying the raw material powder by ball milling in a protective atmosphere to form a phosphorus-based alloy powder. Specifically, the mass ratio of the raw material powder to the grinding ball is 1:12, the ball milling time is 6 hours, the ball milling frequency is 40 Hz, and the protective atmosphere is argon and nitrogen.

[0041] S3, calcination and pore formation: the phosphorus-based alloy powder is calcined at high temperature under a protective atmosphere to form a porous phosphorus-based alloy powder, and after cooling, a porous phosphorus-based sodium ion battery alloy negative electrode material can be obtained. Specifically, the calcination temperature is 640°C, the calcination time is 2h, the heating rate is 6°C / min; the protective atmosphere is argon and nitrogen.

[0042] Example 5 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh red phosphorus and sodium-embedded metal powder and mix them evenly according to a certain proportion to obtain raw material powder. Specifically, the raw material mixing method is ball milling; the molar ratio of red phosphorus to tin powder is 4.

[0043] S2. Alloying treatment: alloying the raw material powder by ball milling in a protective atmosphere to form a phosphorus-based alloy powder. Specifically, the mass ratio of the raw material powder to the grinding ball is 1:17, the ball milling time is 9 hours, the ball milling frequency is 50 Hz, and the protective atmosphere is argon and nitrogen.

[0044] S3, calcination and pore formation: the phosphorus-based alloy powder is calcined at high temperature in a protective atmosphere to form a porous phosphorus-based alloy powder, and after cooling, a porous phosphorus-based sodium ion battery alloy negative electrode material can be obtained. Specifically, the calcination temperature is 630°C, the calcination time is 3h, the heating rate is 7°C / min; the protective atmosphere is argon and nitrogen.

[0045] Application Example 1 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh 1 g of red phosphorus and 4.18 g of tin powder and grind them evenly to obtain raw material powder.

[0046] S2. Alloying treatment: Put the raw material powder into a ball mill, add 55 g of grinding balls, and mill at 45 Hz for 4 h under an argon atmosphere until tin and phosphorus are fully alloyed to form raw material powder.

[0047] S3, calcination and pore formation: calcine the raw material powder in an argon atmosphere, and a porous tin-phosphorus alloy powder material will be formed in the process. The calcination temperature is 590°C, the heating rate is 5°C / min, and the holding time is 2h. After the calcination is completed, it is naturally cooled to room temperature to obtain a porous tin-phosphorus alloy (Sn4P3) material.

[0048] Comparative Example 1 This embodiment relates to a phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh 1 g of red phosphorus and 4.18 g of tin powder and grind them evenly to obtain raw material powder.

[0049] S2. Alloying treatment: Put the raw material powder into a ball mill, add 55 g of grinding balls, and mill at 45 Hz for 4 h under an argon atmosphere until tin and phosphorus are fully alloyed to form raw material powder.

[0050] Application Example 2 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh 2.5 g of red phosphorus and 2.8 g of tin powder and grind them evenly to obtain raw material powder.

[0051] S2. Alloying treatment: Put the raw material powder into a ball mill, add 100 g of grinding balls, and mill at 50 Hz for 6 h in an argon atmosphere until tin and phosphorus are fully alloyed to form raw material powder.

[0052] S3, calcination and pore formation: calcine the raw material powder in an argon atmosphere, and a porous tin-phosphorus alloy powder material will be formed in the process. The calcination temperature is 600℃, the heating rate is 10℃ / min, and the holding time is 1h. After the calcination is completed, it is naturally cooled to room temperature to obtain a porous tin-phosphorus alloy (SnP3) material Comparative Example 2 This embodiment relates to a phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh 2.5 g of red phosphorus and 2.8 g of tin powder and grind them evenly to obtain raw material powder.

[0053] S2. Alloying treatment: Put the raw material powder into a ball mill, add 100 g of grinding balls, and mill at 50 Hz for 6 h in an argon atmosphere until tin and phosphorus are fully alloyed to form raw material powder.

[0054] Application Example 3 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh 3 g of red phosphorus and 2.39 g of antimony powder and grind them evenly to obtain raw material powder.

[0055] S2. Alloying treatment: Put the raw material powder into a ball mill, add 65 g of grinding balls, and mill at 40 Hz for 6 h in an argon atmosphere until antimony and phosphorus are fully alloyed to form antimony-phosphorus alloy powder B.

[0056] S3, calcination and pore formation: calcine the antimony phosphorus alloy powder B in an argon atmosphere, and a porous antimony phosphorus alloy powder material will be formed in the process. The calcination temperature is 650°C, the heating rate is 8°C / min, and the holding time is 3h. After the calcination is completed, it is naturally cooled to room temperature to obtain a porous antimony phosphorus alloy (SbP) material.

[0057] Application Example 4 This embodiment relates to a porous phosphorus-based sodium ion battery alloy negative electrode material, and the preparation method thereof comprises the following steps: S1. Raw material mixing: weigh 1.5 g red phosphorus and 3.97 g tin powder and grind them evenly to obtain raw material powder.

[0058] S2. Alloying treatment: Put the raw material powder into a ball mill, add 80 g of grinding balls, and mill at 45 Hz for 4 h under an argon atmosphere until tin and phosphorus are fully alloyed to form raw material powder.

[0059] S3, calcination and pore formation: calcine the raw material powder in an argon atmosphere, and a porous tin-phosphorus alloy powder material will be formed in the process. The calcination temperature is 630℃, the heating rate is 10℃ / min, and the holding time is 4h. After the calcination is completed, it is naturally cooled to room temperature to obtain a porous tin-phosphorus alloy (SnP) material.

[0060] The porous phosphorus-based alloy materials obtained in the four application examples and the phosphorus-based alloy materials obtained in the two comparative examples mentioned above were characterized differently, specifically: The porous phosphorus-based alloy material, carboxymethyl cellulose CMC and conductive carbon black SuperP obtained in Example 1 were homogenized in a ratio of 7:2:1 and coated, and the phosphorus-based alloy material, carboxymethyl cellulose CMC and conductive carbon black SuperP obtained in Comparative Example 1 were homogenized in a ratio of 7:2:1 and coated. The pole pieces and sodium pieces obtained from the two were assembled in a glove box with a water oxygen value of less than 0.01 ppm to obtain a sodium ion half-cell, and its electrochemical performance was measured on the Xinwei. Specifically, the cycle was carried out at a current density of 1000mA / g to obtain relevant data and compare the cycle performance of the two.

[0061] N2- adsorption-desorption test was performed on both Example 2 and Comparative Example 2 to obtain surface area data of the two and compare their specific surface areas. The SEM data were obtained by performing SEM characterization using Example 3. TEM characterization was performed using Example 4 to obtain TEM data; Figure 1It can be seen that the porous tin-phosphorus alloy carbon composite negative electrode obtained by using Example 1 has better cycle stability, with almost no attenuation during 200 cycles, while the capacity of Comparative Example 1 decays rapidly. This is because the pores provide a buffer space for the volume expansion of the porous tin-phosphorus alloy material, inhibiting the crushing and pulverization of the material, thus having good cycle performance.

[0062] Figure 2 It can be seen that the specific surface area of ​​Application Example 2 is greater than that of Comparative Example 2, because red phosphorus sublimates in situ to form a pore structure during the calcination of the material. The presence of the pore structure increases the specific surface area of ​​the material, thereby increasing the sodium embedding active sites.

[0063] Figure 3 It can be seen from the SEM image that Application Example 3 has an obvious pore structure, which is because the red phosphorus sublimates and forms pores in situ during the calcination process.

[0064] Figure 4 It can be seen from the TEM image that Application Example 4 has an obvious pore structure, which is because the red phosphorus sublimates in situ to form a pore structure during the calcination process of the material.

[0065] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a porous phosphorus-based sodium ion battery alloy negative electrode material, characterized in that The following steps are involved: S1. Raw material mixing: weigh red phosphorus and sodium-embedded metal powder and mix them evenly in proportion to obtain raw material powder; S2. Alloying treatment: alloying the raw material powder by ball milling under a protective atmosphere to form a phosphorus-based alloy powder; S3. Calcination and pore formation: The phosphorus-based alloy powder is calcined at high temperature under a protective atmosphere to form pores to form porous phosphorus-based alloy powder. After cooling, a porous phosphorus-based sodium ion battery alloy negative electrode material can be obtained.

2. The method for preparing the porous phosphorus-based sodium ion battery alloy negative electrode material according to claim 1, characterized in that: In step S3, the calcination temperature is 590-690°C, the calcination time is 1-4h, and the heating rate is 5-10°C / min.

3. The method for preparing the porous phosphorus-based sodium ion battery alloy negative electrode material according to claim 1, characterized in that: In step S2, the mass ratio of raw material powder to grinding balls is 1:10-1:

20.

4. The method for preparing the porous phosphorus-based sodium ion battery alloy negative electrode material according to claim 3, characterized in that: In the ball milling process, the grinding balls are graded with five diameters of 12mm, 10mm, 8mm, 6mm and 4mm; in terms of mass percentage, the grinding balls with diameters of 12mm and 10mm account for 30%~40%, the grinding balls with diameters of 8mm account for 30%~40%, and the grinding balls with diameters of 6mm and 4mm account for 30%.

5. The method for preparing the porous phosphorus-based sodium ion battery alloy negative electrode material according to claim 1, characterized in that: In step S2, the ball milling time is 4-12 hours, and the ball milling frequency is 40-50 Hz.

6. The method for preparing the porous phosphorus-based sodium ion battery alloy negative electrode material according to claim 1, characterized in that: In step S1 , the raw materials are mixed by one or more of ball milling, grinding, and stirring.

7. The method for preparing the porous phosphorus-based sodium ion battery alloy negative electrode material according to claim 1, characterized in that: The sodium embedded metal powder is antimony powder and / or tin powder.

8. The method for preparing the porous phosphorus-based sodium ion battery alloy negative electrode material according to claim 2, characterized in that: In step S1, the molar ratio of red phosphorus to antimony powder is 1-2, and the molar ratio of red phosphorus to tin powder is 0.75-4.

9. The method for preparing the porous phosphorus-based sodium ion battery alloy negative electrode material according to claim 8, characterized in that: In steps S2 and S3, the protective atmosphere is argon and / or nitrogen.

10. A porous phosphorus-based sodium ion battery alloy negative electrode material, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Metal phosphide used as lithium ion secondary battery cathode material and preparation method thereof

    CN101556998A

  • Preparation method of phosphorus / tin / carbon-rich composite negative electrode material

    CN110120504A

  • Preparation method of black phosphorene self-supporting negative electrode material with porous structure

    CN114725362A

  • Composite powder and method for producing the same, negative electrode for secondary battery and secondary battery

    JP2022132194A

  • Positive electrode active material and preparation method therefor, positive electrode sheet, battery, and electric device

    WO2024216581A1

Cited By

  • Phosphorus-based alloy composite negative electrode material and application thereof in all-solid-state secondary battery

    CN121331805A